2006
DOI: 10.1080/10610270500373246
|View full text |Cite
|
Sign up to set email alerts
|

1,1'-Binaphtho(aza)crowns Carrying Photochromic Signalling Unit, I: Synthesis, Characterization and Cation Recognition Properties

Abstract: S)-1,1'-Binaphtho(monoaza)crown-5,-6 and-7 ionophores carrying photochromic indolospirobenzopyran (SP), naphthoxazine (NO) and naphthopyran (NP) signalling groups were synthesized and their cationinduced isomerisation to the colored merocyanine or quinone forms was studied by UV/Vis spectroscopy in the presence of alkali and alkaline earth metal ions. Under dark conditions the equilibrium of SP and NO dyes were remarkably shifted to the colored form by cations of high positive charge density (Li 1 and alkaline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 27 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…SP-1 is an important model of spiropyran type photochromic compounds [10][11][12][13][14][15][16][17]. Various derivatives of SP-1 have been synthesized that form complexes of high stability with metal ions, like the 'bidentate' ligands (they bridge the metal ion by the phenolic oxygen of their MC form and an additional receptive site) [18,19], the multidentate ligands [20,21] and the spiropyrans with attached macrocyclic coordination spheres [22][23][24][25][26]. Görner and Chibisov studying the coordination of metal ions by 'bidentate' spiropyrans in solution, found that the parent compound MC-1 behaves as a 'monodentate' ligand and -like its bidentate derivatives -forms also 1:1 complexes with transition metals [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…SP-1 is an important model of spiropyran type photochromic compounds [10][11][12][13][14][15][16][17]. Various derivatives of SP-1 have been synthesized that form complexes of high stability with metal ions, like the 'bidentate' ligands (they bridge the metal ion by the phenolic oxygen of their MC form and an additional receptive site) [18,19], the multidentate ligands [20,21] and the spiropyrans with attached macrocyclic coordination spheres [22][23][24][25][26]. Görner and Chibisov studying the coordination of metal ions by 'bidentate' spiropyrans in solution, found that the parent compound MC-1 behaves as a 'monodentate' ligand and -like its bidentate derivatives -forms also 1:1 complexes with transition metals [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Beside the parent 1,1 0 -bi-2-naphtho(17-monoazacrown-5)ether, 7 only a few N-substituted fluorescent and photochromic derivatives have been described and their optical responses toward metal ions studied. 7b, 8 It should be noted that none of these molecules have been used as chiral catalysts for asymmetric reactions promoted by alkali bases.…”
Section: Introductionmentioning
confidence: 99%